Application of Ionic Liquids in Biotechnology - Itoh, Toshiyuki; Koo, Yoon-Mo (Advances in Biochemical Engineering/Biotechnology, 2019)
This volume explores how ionic liquids are used in different areas of biotechnology. It also provides insights on the interaction of ionic liquids with biomolecules and biomaterials. Ionic liquids have become essential players in the fields of synthesis, catalysis, extraction and electrochemistry, and their unique properties have opened a wide range of applications in biotechnology. Readers will discover diverse examples of the application of ionic liquids as solvents for biomaterials extraction and pretreatment, in enzymatic and whole cell catalysed reaction, and as activation agents for biocatalysis. Particular attention is given to the biologically functionalized ionic liquids employed in medical and pharmaceutical applications. Although ionic liquids are considered "green solvents", the contributing authors will also explore their environmental impact when applied to biotechnology. Chemical, biological and medical scientists interested in ionic liquids and biotechnology will find this work instructive and informative.